Kemanfaatan, Kemudahan Penggunaan, Perilaku Konsumen, dan Minat Penggunaan E-Wallet - Karina Magdani Andjaniyanto Putri; I Nyoman Rasmen Adi (Universitas Pendidikan Nasional, 2022)
This study aims to examine and analyze the direct effect of usefulness and ease of use on consumer behavior and interest, as well as the indirect effect of usefulness and ease of use on consumer behavior and interest. The research method used is quantitative, with data analysis techniques Structural Equation Modeling (SEM) with SmartPLS. The respondents of this research are the people of Denpasar City who are customers of PT. Bank Pembangunan Daerah Bali Renon Branch Office that uses e-wallet in financial transactions, totaling 90 people. The results showed that the usefulness and ease of use had a positive effect on consumer behavior. While the usefulness and ease of use have a positive effect on interest. Consumer behavior has a positive effect on interest. Consumer behavior is a variable that partially mediates the effect of usefulness and ease of use.